Alternation of nasopharyngeal microbiota in healthy youth is associated with environmental factors: implication for respiratory diseases. - Zhao, Hongcheng; Chen, Shuaiyin; Yang, Fan; Wu, Huiying; Ba, Yue; Cui, Liuxin; Chen, Ruiying; Zhu, Jingyuan (International Journal of Environmental Health Research, 2022)
The nasopharynx is a key niche of the upper respiratory tract which contains many commensal bacteria and potential pathogens. Dysbiosis of the nasopharyngeal (NP) microbiota is associated with a variety of respiratory diseases. Little is known about NP flora in healthy youth, nor about its relationship with environmental factors. We characterized NP microbiota using the 16S rRNA gene sequencing method, and compared microbial composition from subjects sampled in Spring and Fall when exposed to different environmental factors. Results showed that beta diversity was significantly different. Phyla Acidobacteria, Gemmatimonadetes, and genus Symbiobacterium were positively associated with PM2.5. Genera Streptococcus, Prevotella, and [Prevotella] were positively correlated with temperature (T). Ozone (O3) was associated with these floras for exposure that occurred 30 days prior to collection. These preliminary data suggest that the change in environmental factors between spring and fall can influence the composition of the NP microbiota, characterized by a significant correlation to specific taxa. These changes in NP microbiota might be a potential risk factor for respiratory disease.